(untitled) (Texas Journal of Engineering and Technology, 2024)
The investigation of the Internet and computer jargons, analysis of computer and Internet jargons is one of the actual problems within the Uzbek and English languages in comparative way, which is considered to be the first step in Uzbek linguistics.